IMPLEMENTASI METODE PROTOTYPE UNTUK APLIKASI ANDROID MONITORING KULIAH KERJA NYATA PADA STMIK YADIKA BANGIL - Abdul Rokhim; Sultoni Arif Darmawan (STMIK YADIKA BANGIL, 2020)
Abstract : Monitoring is an activity that aims to monitor or observe something. Monitoring must be done directly at the location conducted by officers using tools that provide monitoring data that are general in nature and must be analyzed further, or monitoring data can only be observed locally at the location alone is an obstacle and limitation of the monitoring process. Much time and effort is wasted just on the monitoring process. This research will provide an overview of the use of prototyping models in information systems development activities in the hope that it can produce prototypes as one of the first steps in an information system development activity. The prototype was created with the aim of providing equalization of perception and initial understanding of the basic processes of the system to be developed, so that there will be good communication between developers and system users. The results of this study can be used as a reference or reference for information system developers who have followed the steps in a structured development, so as to provide clarity of the process for users and observers of the science of information systems development. Keywords: monitoring, information systems, prototyping methods, prototypes